2015
DOI: 10.1890/14-1196.1
|View full text |Cite
|
Sign up to set email alerts
|

Early‐season fires in boreal black spruce forests produce pyrogenic carbon with low intrinsic recalcitrance

Abstract: Early-season fires in boreal black spruce forests produce pyrogenic carbon with low intrinsic recalcitrance.Ecology, 96 (6) Abstract. Pyrogenic carbon (PyC), a major by-product of wildfires in boreal forests, plays several critical roles in soil biogeochemical processes. However, PyC properties, including its potential recalcitrance, may vary depending on its formation conditions. Our study aimed to characterize the chemical and physical properties of PyC formed under variable fire severity in Eastern Canada b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…These structural variations are consistent with observations of increasing aromaticity with temperature in laboratory charring studies (Baldock and Smernik, 2002;Czimczik et al, 2002;Ascough et al, 2008;Soucémarianadin et al, 2013;Hart and Luckai, 2014). Organic horizon/biomass char produced in field settings (wildfire or prescribed fire) also shows a range of intensity distributions depending on fire severity, from little alteration to high aromaticity (Nocentini et al, 2010;Miesel et al, 2015;Soucémarianadin et al, 2015b). Similar to laboratory charring, samples referenced to actual temperatures documented in the field show increasing aromaticity with temperature (Alexis et al, 2010;Santín et al, 2016b), and illustrate the variability in formation conditions.…”
Section: Nmrsupporting
confidence: 79%
“…These structural variations are consistent with observations of increasing aromaticity with temperature in laboratory charring studies (Baldock and Smernik, 2002;Czimczik et al, 2002;Ascough et al, 2008;Soucémarianadin et al, 2013;Hart and Luckai, 2014). Organic horizon/biomass char produced in field settings (wildfire or prescribed fire) also shows a range of intensity distributions depending on fire severity, from little alteration to high aromaticity (Nocentini et al, 2010;Miesel et al, 2015;Soucémarianadin et al, 2015b). Similar to laboratory charring, samples referenced to actual temperatures documented in the field show increasing aromaticity with temperature (Alexis et al, 2010;Santín et al, 2016b), and illustrate the variability in formation conditions.…”
Section: Nmrsupporting
confidence: 79%
“…This observation is consistent with the widely accepted paradigm on the chemistry of pyrolyzed materials, suggesting that the aromatic fraction of pyrolyzed material-C increases with formation temperature (Keiluweit et al, 2010). This interpretation is consistent with observations realized using various techniques, including molecular markers (Schneider et al, 2010;Wiedemeier et al, 2015), Fourier-Transform infrared (Keiluweit et al, 2010) and 13 C nuclear magnetic resonance spectroscopy (McBeath et al, 2011;Soucémarianadin et al, 2013Soucémarianadin et al, , 2015Wiedemeier et al, 2015). Also, the pyrolysis of wood has been reported to deliver higher concentrations of aromatic molecules than non-woody materials such as grass (Hammes et al, 2006) or leaves (Singh et al, 2012).…”
Section: Resultssupporting
confidence: 87%
“…Generally, PyC is considered to have a longer mean residence time than non-pyrogenic soil C, typically on the multi-centennial time scale (Hammes et al, 2008;Bird et al, 2015). However, in the past two decades, there has been growing evidence for PyC decomposing on shorter time scales, on the order of days to years (Cheng et al, 2006;Nguyen et al, 2009;Soucémarianadin et al, 2015). Furthermore, Bird et al (2015) suggested a multi-pool model of PyC decomposition, where physical or chemical components of PyC are considerably more susceptible to decomposition than others.…”
Section: Introductionmentioning
confidence: 99%